The spontaneous motion of a slug of miscible liquids in a capillary tube. (2017) - Sellier, Mathieu; Verdier, Claude; Nock, Volker
This contribution explores a droplet actuation mechanism which involves mixing slugs of two different liquids in a glass capillary. The resulting contrast in surface tension which arises provides the necessary propulsive power for the droplet. The conceptual idea is demonstrated for an ethanol-water system. The droplet is observed to rapidly reach a peak velocity which then gradually decreases with time as the two miscible liquids mix. A model is proposed based on Newton's second law which is able to capture the main observed flow phenomena and explain the driving and dissipative mechanisms simultaneously at play in the droplet. This passive actuation mechanism could prove an attractive alternative in digital microfluidics systems for which bulky pumping systems are often required.